Studies on the Identification of Constituents in Ethanol Extract of Radix Glycyrrhizae and Their Anti-Primary Hepatoma Cell Susceptibility. (28th May 2014) - Liu, Jie
Abstract : The objective of this paper is to study the chemical constituents of Radix Glycyrrhizae and to apply the resulting natural products in the study of drug susceptibility of hepatoma cells so as to provide a scientific basis for quality standards and clinical application of medicinal Radix Glycyrrhizae. Chromatographic materials were used for isolation and purification; structural identification was performed based on physicochemical properties and spectral data. MTT colorimetry was used to detect the proliferation inhibition rate against primary hepatoma cells by natural products, and flow cytometry was used to detect the changes in cell cycle progression. Five compounds were isolated and identified, namely, liquiritigenin (1), liquiritin (2), isoliquiritigenin (3), betulinic acid (4), and oleanolic acid (5). In the study, 5-FU (5-fluorouracil) is used as a positive control to the hepatoma cells. Primary hepatoma cells were highly susceptible to 5-FU and liquiritigenin, both of which markedly inhibited the proliferation of hepatoma cells; flow cytometry results showed an increase in G0/G1 phase cells, a decrease in S phase cells, and a relative increase in G2/M phase cells. Primary hepatoma cells are highly susceptible to liquiritigenin, a natural product; the testing of tumor cell susceptibility is of important significance to the improvement of therapeutic effect of cancer.